Socioeconomic differences in dietary habits in Italy before and during COVID-19 pandemic: secondary analysis of a nationwide cross-sectional study - Jacopo Dolcini; Elisa Ponzio; Marcello Mario D’Errico; Pamela Barbadoro (BMC Public Health, 2024)
Abstract Background Several socioeconomic conditions may influence subjects’ adherence to healthy eating habits. Food consumption may be influenced by external stress during crisis periods; however, the effects of these events on food habits are difficult to predict. Also, a pandemic crisis like the recent COVID-19 pandemic may have influenced dietary habits and food consumption. The objective of this study was to compare the dietary habits of Italian people before the COVID-19 pandemic with those belonging to the year 2020 in a nationwide population sample. Materials and methods Information on dietary habits has been obtained from the multi-purpose survey on families’ “Aspects of daily life”, carried out in Italy by the Italian National Statistics Institute (ISTAT). We analyzed data coming from 2016 and 2020 editions of the survey (43,000 subjects each year). We used population attributable fraction (PAF) adjusted for age, defined as the proportional reduction in unhealthy diet that would occur if all participants had had a higher education, assuming higher educated individuals as more socially advantaged. Prevalence association for each dietary exposition has been calculated through logistic regression. Results Looking at aggregated data from 2016 and 2020 both men and women showed a high prevalence of unhealthy dietary habits. Regarding men, excessive consumption of eggs, pork meat, and bovine meat was characterized by a PAF attributable to socioeconomic conditions to an extent greater than 30%. Women showed the same trend. Focusing on different years of investigation, in 2020, during the COVID-19 pandemic, men and women increased their consumption of eggs, cooked fats, snacks, and sweets, and reduced consumption of fruits and vegetables. Additionally, women increased the assumption of dietary products and meat. Both sexes registered an increase in overweight and obese subjects in 2020. Conclusions To our knowledge, this study was the first in our country to use a yearly, nationwide sample to analyze dietary habits by examining specific types of various foods on a nationwide scale and establishing a correlation between these habits and the COVID-19 pandemic. Our results showed unbalanced dietary habits of the Italian population with an excess of consumption of several foods like eggs, cooked fats snacks, and sweets with low consumption of fruits and vegetables. Socioeconomic differences influence food choices but in a complex way since they seemed to affect some wrong dietary habits but not others, especially regarding fruits and vegetables assumption where differences were less evident among social classes. Outside stressors like a crisis period such as the COVID-19 pandemic seem to have an important role in both men and women regarding the assumption of so-called “junk food”.